Fixed-Point Results in Elliptic-Valued Metric Spaces with Applications - Badriah Alamri (Axioms)
The primary objective of this research is to investigate the notion of elliptic-valued metric spaces and prove new fixed-point theorems for diverse generalized contractions. Our contributions extend several existing results in the field. To underscore the novelty of our main result, we provide a concrete example. Additionally, we showcase the practical relevance of our primary theorem by solving a Urysohn integral equation.